Clinical Efficacy and Safety of Different Doses of Sildenafil in the Treatment of Persistent Pulmonary Hypertension of the Newborn: A Network Meta-analysis - Sun, Linli; Wang, Chunxia; Zhou, Yulu; Sun, Wei; Wang, Chunjiang (Frontiers in Pharmacology, 2021)
Objective: To evaluate the efficacy and safety of different doses of sildenafil for persistent pulmonary hypertension of the newborn (PHNN) with a network meta-analysis. Methods We searched Chinese and English databases for randomized controlled trials (RCTs) concerning sildenafil in newborns with persistent pulmonary hypertension. Results Twenty-two RCTs including over 2131 patients were included. The network meta-analysis revealed that 1.5 mg/kg of sildenafil led to a significant decrease in systolic pulmonary arterial pressure (sPAP) compared with 0.3 mg/kg and 0.6 mg/kg (P<0.05); 1.5 mg/kg was better than 0.3 mg/kg, 0.5 mg/kg, and1.0 mg/kg at increasing the partial pressure of oxygen (PaO2) (P<0.05); 1.5 mg/kg was better than 0.5 mg/kg, 0.6 mg/kg and 1.0 mg/kg at reducing the partial pressure of carbon dioxide (PaCO2) (P<0.05); and 1.2 mg/kg was better than 0.3 mg/kg, 0.5 mg/kg and 1.0 mg/kg at increasing the arterial oxygen saturation (SaO2) (P<0.05). The surface under the cumulative ranking analysis (SUCRA) results showed that 1.5 mg/kg had the best effect in reducing sPAP (SUCRA=92.0%) and PaCO2 (91.1%) and increasing PaO2 (SUCRA=79.3%), 2.0 mg/kg had the best effect in increasing SaO2 (SUCRA=88.6%) and clinical efficacy (SUCRA=93.5%). No severe adverse effects were observed with the different doses of sildenafil. Conclusion: Different doses of sildenafil can significantly improve PPHN, and 1.5 mg/kg of sildenafil has better clinical efficacy and does not increase the probability of adverse reactions.